2016
DOI: 10.1039/c6ra22920d
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal synthesis of flower-like CoS hollow microspheres with excellent microwave absorption properties

Abstract: In this study, flower-like CoS hollow spheres (CHSs), synthesized via a facile solvothermal method in the presence of CTAB, were initially investigated as microwave absorbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Our group synthesized a series of CuS particles with multistage nanostructures by a simple wet chemical method, and the CuS-PVDF composites (5 wt%) achieved the minimum reflection loss of À 102 dB at 7.7 GHz with thin absorber thickness of 3.5 mm. [28] Other metal sulfides have also shown great potential in this field, such as CdS, [29] ZnS, [30] CoS, [31] PbS [32] etc. Among these TMDCs, nickel-sulfur compounds exhibit a variety of phases and structures because the valence state of nickel is easy to adjust, which result in coexisting of many phases in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Our group synthesized a series of CuS particles with multistage nanostructures by a simple wet chemical method, and the CuS-PVDF composites (5 wt%) achieved the minimum reflection loss of À 102 dB at 7.7 GHz with thin absorber thickness of 3.5 mm. [28] Other metal sulfides have also shown great potential in this field, such as CdS, [29] ZnS, [30] CoS, [31] PbS [32] etc. Among these TMDCs, nickel-sulfur compounds exhibit a variety of phases and structures because the valence state of nickel is easy to adjust, which result in coexisting of many phases in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao and co-workers 2 have constructed hierarchical hollow CuS microspheres and found that the minimum reection loss of paraffin-based composites (50 wt%) is À17.5 dB and the effective bandwidth is 3.0 GHz with thin absorber thickness of 1.1 mm. Other metal suldes such as CdS, 19 Bi 2 S 3 , 20 CoS, 21 PbS, 22 NiS 2 @MoS 2 , 23 etc. have been demonstrated as novel microwave absorbers with a remarkable reection loss.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have been devoted to the synthesis of EA materials to obtain EA materials having properties such as strong absorption capability, wide effective absorption bandwidth, high thermal stability, lightweightedness, and anti-oxidation. [6][7][8] With the development of technology, various strategies have been explored to synthesize functional materials to achieve better EA performance; these materials include metal oxides or suldes, such as ZnO, 9 CoFe 2 O 4 , 10 SnO 2 , 11 CoS, 12 and CuS 13-15 as well as carbon materials such as carbon nanotubes (CNTs), 16,17 graphene or reduced graphene oxide (RGO), 18 carbon bers (CFs), 19 and/or their hybrids. 20,21 Among the many existing materials, heterostructures of magnetic loss-type and dielectric loss-type materials produce great enhancement in EA performance; these materials include Fe 3 32 graphene CuS, 33 and CuS/ ZnS.…”
Section: Introductionmentioning
confidence: 99%